Dynamics of hematological parameters and oxidative stress markers in Ukrainian warmblood horses under exercise influence - Андрійчук, А. В.; Ткаченко, Г. М.; Кургалюк, Н. М.; Ткачова, І. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
The aim of this study was to analyze changes of the oxidative stress markers (levels of malonic dialdehyde, lipid hydroperoxides, middle molecules, aldehyde and ketonic derivates of oxidatively modified proteins) and hematological parameters in Ukrainian warmblood horses under the training. Significant changes in counts of red blood cells, hemoglobin, hematocrit and subpopulations of leukocytes, as well as platelets after the exercises were observed. This could indicate about adaptive responses of the blood system to maintain homeostasis to systematic training and physical activity. There was significant decrease in the thiobarbituric acid reactive substrates (TBARS) content and the lipid hydroperoxides level in the erythrocytes and plasma of Ukrainian warmblood horses after training. Significant decrease of the aldehyde derivatives of protein oxidation level in the plasma after training occurred. The level of oxidative stress markers and hematological parameters of sport horses can be sensitive and informative indicators for the assessment of horse’s performance.